Development of Technology for Functional Confectionery Products - Ashurova M. Z.; Sulaymanova G. X. (Research Parks Publishing LLC, 2021)
The questions about the special role in the rational health food of the population are given to the creation of fundamentally new, balanced in the composition of products, enriched functional ingredients. Taking into account the chemical composition and technological properties of vegetables and vegetable pastes, vegetables that help to increase the nutritional value of finished products can be promising enhancers of the quality of flour confectionery products.